Rela????o entre cifose dorsal, densidade mineral ??ssea e risco de quedas em idosas - Regolin, Fabiana (2009)
Introduction: The increase of dorsal kyphosis is frequent for elderly people. This posture deformity can be caused both by osteoporotic and non-osteoporotic conditions. Regardless its origins, the increase of dorsal kyphosis has been considered an intrinsic factor for the elderly to fall. A variety of instruments is available to evaluate posture control, including the posturography and the Time Up and Go clinical test. Objectives: Verify and analyze the influence of the angular measure of dorsal kyphosis and of the osseous mineral density on the risk of elderly women to fall. Materials and Methods: The research was a cross-sectional study, had evaluated 95 elderly women in two steps. First, the measurement of the dorsal kyphosis??? angle, using the flexicurve method. Then, the Time Up and Go test, and the collection of data using a stabilometer. Each patient was submitted to Folstein Mini Mental Status Examination. On the second phase of the research, each elderly woman had her osseous densitometry examined. Considering the measured curves of dorsal kyphosis and the interpretation of osseous densitometry, the participants were divided into four groups: first, those who lost osseous mass and whose dorsal kyphosis increased; second, those who lost osseous mass but whose dorsal kyphosis did not increase; third, those who did not lose osseous mass and whose dorsal kyphosis did not increase; and fourth, those whose dorsal kyphosis increased, but did not lose of osseous mass. The performances of each group, at the static force platform and at the Time Up and Go test, were then statistically analyzed and compared. Results: At the static force platform, there was significant statistical difference only between the first and the third group, in the antero-posterior direction (p=0,0124), as well as the third group was the only one that exhibited homogeneous performances with eyes opened and eyes closed, in the medial-lateral direction (p=0,4263). Meanwhile, in the anteroposterior direction, no group exhibited any difference between both tries (p 0,6298). Concerning the Time Up and Go test, the group 4 (with loss of osseous mass and without increase of dorsal kyphosis) has achieved the best performance (12,6s). Conclusions: The angular measure of dorsal kyphosis and the osseous mineral density were co-related to the risk of falling, statically, in the antero-posterior direction. During the dynamic posture, the risk of falling was co-related to age.